Infection Control Practice in Postmortem Evaluation of the Crimean Congo Hemorrhagic Fever Cases - Keten, Alper; Tümer, Ali Rıza; Odabaşı, Aysun Balseven; Keten, Derya (The Bulletin of Legal Medicine, 2008)
Unless post-mortem examinations are perfomed in adequate circumstances, there may be some life-threatening infectious risks for both the forensic medicine staff and for the environment. In last few years there was an increasing number of deaths due to the Crimean-Congo hemorrhagic fever in Turkey. We aimed to observe the rules that should be followed to minimize the risks of the autopsy on Crimean-Congo hemorrhagic fever cases in which there is a high risk of infection. Key words: Autopsy, Crimean-Congo hemorrhagic fever, prevention